PSYCHOLOGICAL FEATURES OF SOCIALIZATION AND COMMUNICATION OF PRESCHOOL CHILDREN WITH THE 3RD LEVEL OF GENERAL UNDERDEVELOPMENT OF SPEECH - Andreiko, Bohdanya; Dmytriv, Yuliia (PSYCHOLOGICAL JOURNAL, 2019)
Nowadays, there are a large number of children with speech disorders in educational institutions, in which there are secondary violations in cognitive activity, emotionally-volitional sphere and in behavior. However, mostly in such children there are primarily violations of socialization and communication. Children,with special educational needs, with disturbed psychophysical development or speech disorders, staying in an inclusive environment, in a educational-rehabilitation center, or in a secondary school, are there with themselves. Often, realizing their own features, they do not want to join the group, realizing that something "wrong" with them, they are "not like" other children, they look differently, they need more time to master the material, and their speech is distinguished by coevals. However, each child is special, each child has a certain resource through which a teacher, correction teacher and other specialists will be able to help her socialize and teach her to communicate and interact with other children. It is also necessary to remember the paramount role of parents in correctional and educational work with a child with violations. The teacher should act as an example for imitation among children, to be a model of speech activity and behavior. Parents should be involved in the active correction process, since the work of parents is the key to the successful and effective socialization and communication of their children. The effectiveness of correction of the processes socialization and communication of children with the 3rd level of general underdevelopment of speech is determined, first of all, by the degree of effectiveness of speech therapy work on all spheres of speech activity: vocabulary, grammar, sound phonemic-phonematic processes and coherent speech. However, already in the process of conducting speech therapists it is necessary to work out communication of the child, and work on its socialization. It is important to note the peculiarities of the emotional and volitional sphere of the child with speech disorders by the psychologist, in order to increase self-esteem, reduce anxiety, overcome secrecy in communication and social relationships with other children.